Peryodismo sa bingit mga naratibong ulat sa panahon ng digmaan at krisis - Guda, Kenneth Roland A. (Diliman, Quezon City University of the Philippines Press, 2016)
Reports in newspapers during the war and crisis in the Philippines.
Includes index.
In Tagalog
Keywords: War -- Press coverage -- Philippines; Crises -- Press coverage -- Philippines; Newspapers -- Sections, columns, etc